Respect, Protection, and Fulfillment of the Right to Freedom of Religion in a Pancasila-based Legal System - Delpedro Marhaen; Sitabuana, Tundjung Herning (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
The significance of this research stems from the prevalence of religious freedom violations in Indonesia, indicative of the inadequate level of respect, protection, and fulfillment of this entitlement within the framework of the Pancasila legal system. This study aims to ascertain how to effectively uphold, safeguard, and fulfill the right to freedom of religion within the Pancasila Rule of Law. Utilizing normative juridical research methods, the findings reveal a discrepancy within the legal norms governing religious rights in the Constitution. While Article 28I, paragraph (1) of the 1945 Constitution unequivocally affirms the inviolability of the right to religion under any circumstances, Article 28J, paragraph (2) of the same Constitution delineates that this right is subject to limitations regulated by law. The research concludes that, despite its normative recognition as an inherent entitlement, numerous violations of religious freedom persist in Indonesia in practical application.